(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The uncertainty of the business environment increases the volatility of business competition, which in turn forces organizations to always rethink their strategies since they have to deal with the changes in their business environment. The ability of an organization to adapt to a certain change in the business environment will determine whether they are ready or not to face the changes. The extent of this readiness is actually a reflection of organizations’ ability to meet the dynamic change in the environment. Organizations that are ready for change will have more advantages compared to organizations that are not ready. The organization should understand important factors that could determine this readiness. This research aims to explore the effect of learning on organizations’ readiness for change. Data was collected from 124 respondents that responded to this research questionnaire. The finding shows learning organization significantly influences organizational readiness for change.